Creating your world : - Weber, Aimee (Wiley Pub., 2008)
Enrich your virtual existence by mastering the techniques and tactics the experts use to create jaw-dropping SL content—everything from buildings and vehicles to clothing, landscapes, and animations. This official, exclusive guide from a team of Second Life content-creation experts was written with the full support of Linden Lab and features in-depth instructions for creating beautiful content and putting it to work in-world. It’s both a practical, step-by-step guide and a creative session with some of the most artistic and talented minds in the Second Life community. CD included.